2016
DOI: 10.1016/j.jaip.2015.11.031
|View full text |Cite
|
Sign up to set email alerts
|

African American Patients with Chronic Rhinosinusitis Have a Distinct Phenotype of Polyposis Associated with Increased Asthma Hospitalization

Abstract: BACKGROUND Chronic rhinosinusitis (CRS) is a common inflammatory disease of the upper airways that is often categorized into subtypes including “with” and “without” nasal polyps. However, the influence of multiple important epidemiologic factors, including race, on CRS has not been investigated. OBJECTIVE The present study assessed various phenotypic characteristics of CRS in patients, living in the United States, with different racial backgrounds. METHODS We performed a large retrospective cohort study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 27 publications
(38 reference statements)
2
20
1
Order By: Relevance
“…43,44 African-American patients also seem to have more severe sinus disease. 45 Our study indicates that similar disparities exist in AERD, specifically with regard to aspirin treatment outcomes.…”
Section: Discussionsupporting
confidence: 61%
“…43,44 African-American patients also seem to have more severe sinus disease. 45 Our study indicates that similar disparities exist in AERD, specifically with regard to aspirin treatment outcomes.…”
Section: Discussionsupporting
confidence: 61%
“…Those African-American CRS patients with polypoid disease had a history of more hospitalizations for asthma. These findings suggest that African-Americans, who are known to have higher prevalence and worse severity of asthma, also have worse CRSwNP than patients from other races (167). Pinto et al (168) reported that African-American CRS patients had lower vitamin D levels than control African-American patients, and Bush et al (169) reported that surgical outcomes were not as durable in African-American patients with polypoid CRS and asthma compared with Caucasian patients.…”
Section: Race Eosinophilia and Crs: What Are The Roles Of Genes Andmentioning
confidence: 90%
“…We previously found that the phenotype of CRS is different and more severe in African Americans. 16 African American patients with CRS have a higher CRS severity index on computed tomography (LMS) and increased smell loss than white patients with CRS. 16 In our current study, no association was found between OSA and higher LMS.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the medical records of all patients in our previously reported large retrospective cohort of CRS. 16,17 CRS was diagnosed per the American Academy of Otolaryngology–Head and Neck Surgery Chronic Rhinosinusitis Task Force criteria, 18 with more than 12 weeks of continuous rhinosinusitis symptoms, along with nasal endoscopy or computed tomography demonstrating objective findings of sinusitis.…”
Section: Methodsmentioning
confidence: 99%